A Widely Distributed Thraustochytrid Parasite of Diatoms Isolated from the Arctic Represents a gen. and sp. nov. - Hassett, Brandon (Journal of Eukaryotic Microbiology, 2020)
A unicellular, heterotrophic, eukaryotic parasite was isolated from nearshore Arctic marine sediment in association with the diatom Pleurosigma sp. The parasite possessed ectoplasmic threads that could penetrate diatom frustules. Healthy and reproducing Pleurosigma cultures would begin to collapse within a week following the introduction of this parasite. The parasite (2–10 μm diameter) could reproduce epibiotically with biflagellate zoospores, as well as binary division inside and outside the diatom host. While the parasite grew, diatom intracellular content disappeared. Evaluation of electron micrographs from co‐cultures revealed the presence of hollow tubular processes and amorphic cells that could transcend the diatom frustule, generally at the girdle band, as well as typical thraustochytrid ultrastructure, such as the presence of bothrosomes. After nucleotide extraction, amplification, and cloning, database queries of DNA revealed closest molecular affinity to environmental thraustochytrid clone sequences. Testing of phylogenetic hypotheses consistently grouped this unknown parasite within the Thraustochytriidae on a distinct branch within the environmental sequence clade Lab19. Reclassification of Arctic high‐throughput sequencing data, with appended reference datasets that included this diatom parasite, indicated that the majority of thraustochytrid sequences, previously binned as unclassifiable stramenopiles, are allied to this new isolate. Based on the combined information acquired from electron microscopy, life history, and phylogenetic testing, this unknown isolate is described as a novel species and genus.